2015
DOI: 10.1038/pr.2015.227
|View full text |Cite
|
Sign up to set email alerts
|

Fast Doppler as a novel bedside measure of cerebral perfusion in preterm infants

Abstract: Background: Altered cerebral perfusion from impaired autoregulation may contribute to the morbidity and mortality associated with premature birth. We hypothesized that fast Doppler imaging could provide a reproducible bedside estimation of cerebral perfusion and autoregulation in preterm infants. Methods: This is a prospective pilot study using fast Doppler ultrasound to assess blood flow velocity in the basal ganglia of 19 subjects born at 26-32 wk gestation. Intraclass correlation provided a measure of test-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…We found good intraobserver repeatability with US imaging of the thalamus in this primate model of HIE, which was consistent with our previous report on imaging the human basal ganglia 12 as well as reports on other cerebral hemodynamic measures, such as superior vena cava flow. 19 The thalamus RI measures did not show an improved ability to predict outcomes over anterior cerebral artery measures, but they had a consistently stronger association with clinical measures of disease severity, such as serum and MRS lactate, outside the first 24 hours of life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found good intraobserver repeatability with US imaging of the thalamus in this primate model of HIE, which was consistent with our previous report on imaging the human basal ganglia 12 as well as reports on other cerebral hemodynamic measures, such as superior vena cava flow. 19 The thalamus RI measures did not show an improved ability to predict outcomes over anterior cerebral artery measures, but they had a consistently stronger association with clinical measures of disease severity, such as serum and MRS lactate, outside the first 24 hours of life.…”
Section: Discussionsupporting
confidence: 91%
“…This speed allows for high sensitivity, especially in deeper tissues, and the ability to quantify flow information over entire regions of interest. Our group previously demonstrated that fast Doppler US could effectively measure blood flow velocities in the deep gray matter of human neonates . We hypothesized that measuring the RI at the level of the thalamus using fast Doppler US in a nonhuman primate model of HIE would show a stronger association with adverse neurologic outcomes, clinical illness severity, and death than measuring the RI in the anterior cerebral artery.…”
mentioning
confidence: 99%
“…Several prior studies have assessed cerebral brain perfusion in the neonate using various techniques such as cerebral artery Doppler, near-infrared spectroscopy, PET, and xenon-enhanced CT. [8][9][10][11] These techniques lack anatomic detail, use indirect cerebral perfusion measurements, and/or have a risk of radiation or the need for intravenous contrast. [12][13][14] Conversely, in the present study, we used the arterial spin-labeling (ASL) MR imaging technique, which has recently emerged as a promising noninvasive method for direct quantitative assessment of cerebral perfusion in high-risk neonates, including neonates with perinatal stroke 15 or hypoxic-ischemic encephalopathy, 16 without radiation risk or the need for intravenous contrast.…”
mentioning
confidence: 99%
“…There is also evidence of a significant cerebral hypoxic burden in many preterm infants over the first days after birth (22). In addition, cerebral autoregulation is inconsistent in very preterm infants (20,23). Together, these factors suggest that low cerebral blood flow could contribute to the high disability rate experienced by preterm newborns (2).…”
Section: Discussionmentioning
confidence: 99%